Danao the parrot - Shaw, Rachel. L. (The Bookmark, 2015)
"Danao the Parrot - a story celebrating the unique wildlife of the Philippines. A house in a city isn't the place for a parrot to be. But where should a parrot live? Join a little parrot called Danao on his amazing journey across the Philippines in search of the perfect place to live. Along the way he meets a lot of other animals from tarsiers and cloud rats to Philippine eagles and crocodiles. Many of these animals, like Danao, are found only in the Philippines."